SEKOLAH VERSUS PESANTREN SEBUAH PERBANDINGAN MENUJU FORMAT BARU MAINSTREAM LEMBAGA PENDIDIKAN NASIONAL PENIADA DIKOTOMIK - Amrizal Amrizal (Sosial Budaya, 2011)
Sekolah-Pesantren is an ideal educational institution for Indonesia that was carried into the new maintream Indonesian national education system. Integrating and choices of both institutions is done because it has a fundamental difference conflicting; sekolah has an advantage in the development of science and technology but failed in the moral and character development, while pesantren, on the contrary, is known to have experience and success in coaching morale and akhlak of the it’s student but not capable in developing science and technology. Praxis sekolahpesantren rests on the basic concept of human. The formulation of the vision, mission, and goals sekolah-pesantren is so likewise with the technique and metode used in the learning process, all remain within the framework of development and empowerment of students' potentials as human beings. Thus, sekolah-pesantren are expected to become an ideal educational institution nondikotomik.